Preparatory Examination in Civil Procedure Law: Strategies for Swift and Efficient Justice - Hidayat, Imam; Abdul Rachmad Budiono; Budi Santoso; Rachmi Sulistyarini (Universitas Muhammadiyah Malang, 2024)
The rigidity of formal requirements in civil litigation in Indonesia has resulted in numerous cases being dismissed as